Follow up and behavior of pediatric home admission in San Lazaro´s popular council in Cienfuegos Province. - Caridad Hernández Gutiérrez; Carmen E. Guerra Cabrera; Teresita Rodriguez Izaguirre; Roxilena Manso Martín (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2004)
Fundaments: The development of Public Health in Cuba, especially in public health assistance has permitted the rescue of old modalities in regards to medical assistance, among of them home admissions, procedure that has its origin in our ancestors but now with the distinctive features of the ways of medical assistance, social system and economic resources among others. Objective: To assess the behaviour and follow up of paediatric home admissions in San Lázaro Popular Council. Method: Retrospective study of all the patients aged 0-14 years with home admissions in San Lázaro Popular Council who belong to the teaching policlinic ¨Octavio de la Concepción y de la Pedraja¨ from Cienfuegos Municipality, from January to December 2002. The variables under study were: age, sex, nutritional assessment , cause of admission, admission by the general comprehensive doctor, hospital discharge, follow up, complications and stay. Results: short age was a determinant factor in home admissions: 78,4 % of the admitted patients were eutrophic; respiratory infections and acute diarrheas were the main reasons for admissions